The Faktor-Faktor Yang Berhubungan Dengan Kejadian Anemia Pada Remaja Putri - Amalia, Naila; Wulandari Meikawati; Rokhani (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2024)
Anemia is a condition where the hemoglobin level in the blood is below normal levels. Adolescent girls are at higher risk of experiencing anemia due to menstruation which has an impact on decreasing academic abilities and in the long term has the potential to increase the risk of maternal death and giving birth to Low Birth Weight (LBW). Based on 2023 data, the incidence of anemia in the UPTD of Godong 1 Community Health Center is still high, namely 176 cases. The aim of this research is to identify factors associated with the incidence of anemia in adolescent girls at Madrasah Tsanawiyah Yatpi Godong in 2024. This type of research is analytical observational with a cross-sectional approach. The population is adolescent girls in grades 7-9 WHO attend Madrasah Tsanawiyah Yatpi Godong with a total of 115 people. The sample was 54 people selected using proportional random sampling technique. The instruments used consisted of a questionnaire (knowledge of anemia, compliance with the consumption of Iron Tablets Supplementation and the menstrual cycle), anthropometric measuring instruments (scales, microtoise and LILA tape) and easy touch Hb (to measure levels Hb). Data were analyzed using the chi-square test. The majority of respondents had anemia as much as (72.2%), low knowledge of anemia (51.9%), thinness (59.3%), chronic energy deficiency (57.4%), and non-compliance with taking Iron Tablets Suplementation (75.9%). It was found that 20.4% of respondents experienced abnormal menstrual cycles. This research shows that there is a correlation between nutritional status, compliance in consuming Iron Tablets Supplementation, and the menstrual cycle with the incidence of anemia. However, there was no significant relationship between knowledge and the incidence of anemia in adolescent girls.